Simulations of filter media performances from microtomography-based computational domain. Experimental and analytical comparison. (15th August 2015) - Gervais, P.-C.; Bourrous, S.; Dany, F.; Bouilloux, L.; Ricciardi, L.
Highlights: Synchrotron X-ray microtomography is used to produce images of fibrous filter media. Representative domains are created with the importation interface of GeoDict. Flow and efficiency simulations are carried out thanks to GeoDict. Good agreement is found between experimental and simulated values of permeability. Simulated values of efficiency tend to underestimate the experimental ones. Abstract: In this work, synchrotron X-ray microtomography was used to produce high spatial resolution images of one fibrous filter, made of binderless monodispersed fiberglass. Based on these images, representative computational domains were created using the import interface of the GeoDict software. Both flow and collection efficiency simulations were then carried out using the CFD modules of GeoDict. In parallel, permeability and collection efficiency measurements were performed on the same media, to provide an experimental comparison. A very good agreement was found between the experimental and simulated permeability values. However, simulated efficiency values tend to underestimate the experimental ones. In the second part of the paper, an image analysis program based on Matlab® was used to determine the structural properties of the fibrous structures, namely the thickness, the solid volume fraction and the fiber size distribution. These data were introduced into analytical models that successfully predict the permeability and collection efficiency values.